Sistema simulador de redes y ruteo virtual. - Jaramillo Ramírez, Magaly Elizabeth (2010)
The present research work is based on the creation of a network simulating system and virtual routing. It is a tool for professionals, students from the systems and telecommunications area who want to venture into the field of data transmission networks, or those who simply want to acquire better skills at creating networks (networking). The system will have a friendly, graphic interface which will allow the user to move network devices such as Routers, Pc’s, switches to any place on the screen. It will allow to create networks according to the necessity, and it will allow to have physical connection through lines, and in this way to simulate the desired network. The network simulating system and virtual routing will be focused on the configuration of the router, that is to say, the system will have the capacity to set up the important characteristics of the router through well-known commands for the configuration of the router, CISCO brand, 2500 family. It will allow to set up each interface such as the Ethernet O, Serial O, Serial 1 as well as the routing table for the interface. The user of this system will be able to set up the NIC of the host, which is understood by the IP, mascara, gateway. The switch device will have the capacity of interacting as a layer 2 device, OSI model. In order to be able to verify that the configuration of the system is right, the system will foresee to enable test commands such as the ping command, trace router, and the Telnet command which allow us to verify if the data network is set up correctly. In this way, the network simulating system and virtual routing will allow the user to create his data network, do tests, and determine if its configuration is according to his necessities and convenience. The system will be able to present a report of the configurations of the routers and used hosts. Besides it will have the option to print such report to be presented to whom it may concern, as well as the printing of the data network. The system will have the capacity to continue growing with additional modules, that is, the system is intended to be approachable according to user’s necessities.